Factors Affecting Antibiotic Decisions for Upper Respiratory Tract Infections I:A Survey of Family Physicians - Zoutman, Dick E; Douglas Ford, B; Bassili, Assil R; Cosby, Jarold L; Nakatsu, Kanji (International Journal of Infection Control, 2008)
Identifying factors associated with the ubiquitous inappropriate prescribing of antibiotics for upper respiratory tract infections (URTIs) will help develop effective interventions and decrease antimicrobial resistance. Surveys were mailed to family physicians in Ontario, Canada. The survey assessed antibiotic prescribing for URTIs and a wide range of influences on antibiotic decisions. Multivariate models of inappropriate prescribing were generated. 316 of 544 (58%) family physicians completed surveys. Associated with self-reported antibiotic prescribing for acute bronchitis were patients with obligations (OR 2.1; 95% CI, 1.2-3.6), physicians with positive antibiotic use attitudes (OR 2.1; 95% CI, 1.1-3.9), satisfaction antibiotics best for patients (OR 1.5; 95% CI, 1.1-2.1), and knowledgeable patients (OR 0.5; 95% CI, 03-0.8). Associated with antibiotic prescribing for influenza were patients with obligations (OR 2.2; 95% CI, 1.2-3.8), patients thought to be seeking antibiotics (OR 1.4; 95% CI, 1.1-1.9), and attending university and profession sponsored courses (OR 0.7; 95% CI, 0.4-1.0). Associated with not prescribing first line antibiotics for acute sinusitis were pharmaceutical industry influence (OR 2.0; 95% CI, 1.1-3.3), solo practice (OR 2.0; 95% CI, 1.1-5.0), and recommending rest and simple analgesics (OR 0.5; 95% CI, 0.3-0.8). Associated with not prescribing first line antibiotics for streptococcal pharyngitis were pharmaceutical industry influence (OR 1.7; 95% CI, 1.3-2.5), physician age (OR 1.6; 95% CI, 1.3-2.1), and perceived importance of clinical guidelines (OR 0.6; 95% CI, 0.4-0.8). Health care workers should be informed of the influence of perceived patient motivation and the pharmaceutical industry on antibiotic use for URTIs and these insights included in interventions targeting inappropriate antibiotic prescribing.